A Comparative Analysis of Pre -School Education In Learing Environment: Research and Policy Effects: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Over the last several decades, participation incenter-based preschool programs has become much more common, and public supportfor these programs has grown dramatically. Nevertheless, participation remainsfar from universal, and policies vary across states, as well as across optionssuch as private child care, preschools, Head Start, and state pre-K. Since policy makers typically have more alternatives thanmoney, they face key questions about the value of preschool education, whom itshould serve or subsidize, and which program designs are best. This briefreviews the research regarding the short- and long-term effects of preschooleducation on young children’s learning and development. A detailed andcomprehensive assessment of evidence yields the following conclusions andrecommendations: The idea of state-funded universal preschool has startedto gain traction in recent years. Iowa already has a system in place to meetthe needs of many preschool children; however, as of recent, the current systemis in funding jeopardy. Nebraska, on the other hand, does not have universal preschoolavailable to its children and it is struggling to meet the needs of K-5education funding. Each state struggles with the benefits versus the costs ofpreschool education for the state’s children. This research brief will reviewthe benefits of a preschool education as well as examine what the research saysabout fading effects on academic skills for students who attend preschool. Thisresearch brief will also highlight promising practices in eliminating fadingacademic effects in students who attend preschool in comparison to students whodo not attend preschool.